Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

If f(x) = x3 – 7, show that f-1(x) = Vx+7.


Sagot :

Answer:

f(x)=4−(x−7)

3

Let y=f(x)

So, x=f

−1

(y) ---- ( 1 )

y=f(x)

⇒ y=4−(x−7)

3

⇒ (x−7)

3

=4−y

⇒ x−7=

3

4−y

⇒ x=7+

3

4−y

⇒ f

−1

(y)=7+

3

4−y

.................. [ From ( 1 ) ]

∴ f

−1

(x)=7+

3

4−x